Urban forestry in Kathmandu valley: problems and prospects - Gautam, SK; Thapa, HB; Sharma, RC (Banko Janakari, 2008)
A survey was carried out to find problems and prospects of urban forestry in Kathmandu Metropolitan city. The methodology includes road side survey, direct observation and discussion with local people. Many problems were identified such as poor management of the planted species, risk of tree hazard, and lack of proper coordination among stakeholders, low priority in planning, and stumpy financial resources. Moreover, there is a great potential to promote urban forestry as people’s perceptions regarding participation is quite positive. This paper presents an overview of urban forestry activities and some points related to promotion of urban forestry in the Kathmandu valley. Key words: Urban forestry; tree hazard; people’s participation; environment management Banko Janakari Vol.16(2) 2006 pp.64-70